Hari Raya Aidilfitri Celebrating Faith, Gratitude, and Compassion - Amy Zulaikha, Mohd Ali (UMPSA, 2024)
Blessings and salutations to the Prophet Muhammad PBUH, his families, companions, and all those who follow his teachings to the day of judgment. First and foremost, hope it is not too late to wish رَمَضان المُبارَك ‘Blessed Ramadhan’ to UMPSA staff and students. May Allah reward us with التَّقْوَىٰ so that we may express our gratitude for the blessing of guidance Allah has blessed us all with.